REVITALISASI PEMASARAN PRODUK APEL OLAHAN DAN IMPLIKASINYA TERHADAP STRATEGI DAN BAURAN PEMASARAN PT. KUSUMA SATRIA DINASARI WISATAJAYA - MALANG - fredi andria (Jurnal Sosial Humaniora, 2010)
The purposes of this study are: (1) to analyse the marketing strategy of processed apple of PT. Kusuma Agrowisata; (2) to analyse the industry competitive's condition of processed apple produced by PT Kusuma Agrowisata; and (3) to recommend strategies and marketing mix alternatives to be implemented by PT Kusuma Agrowisata in order to achieve their missions and vision. All of these purposes are focused on marketing revitalization for PT Kusuma Agrowisata. A competition analysis (Five Force's of Proter) with Delphi Technique and SWOT analysis is used. A marketing strategy and marketing mix would be formulated for all processed apples as by PT Kusuma Agrowisata, Malang as recommende